2007
DOI: 10.1158/0008-5472.can-06-3955
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Inhibits Inflammatory and Angiogenic Attributes in Photocarcinogenesis in SKH-1 Hairless Mice

Abstract: Sunscreens partially filter UVB and, therefore, could partially prevent skin cancer; however, efficient approaches are desired to effectively prevent photocarcinogenesis. It is hypothesized that nontoxic pharmacologically active natural compounds can increase photoprotective effects. Our completed studies suggest that silibinin, a bioactive phytochemical, strongly prevents photocarcinogenesis; however, its mechanism is not fully understood. Herein, for the first time, we used a clinically relevant UVB dose (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
144
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 50 publications
5
144
0
Order By: Relevance
“…Immunohistochemical Analysis Paraffin-embedded, 5-Am-thick sections were deparaffinized and stained with primary antibodies anti -proliferating cell nuclear antigen (PCNA; DAKO) and anti-survivin (Novus) followed by 3,3-diaminobenzidine staining as recently published (15). The immunostained cells were quantified by counting the brown cells and the total number of cells at five randomly selected fields at Â400 magnification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical Analysis Paraffin-embedded, 5-Am-thick sections were deparaffinized and stained with primary antibodies anti -proliferating cell nuclear antigen (PCNA; DAKO) and anti-survivin (Novus) followed by 3,3-diaminobenzidine staining as recently published (15). The immunostained cells were quantified by counting the brown cells and the total number of cells at five randomly selected fields at Â400 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot Analysis of Tissue Lysates Total tissue lysate and nuclear lysate were prepared as earlier published (15). Protein concentration in tissue lysates was determined with Bio-Rad detergent-compatible protein assay kit (Bio-Rad Laboratories) by the Lowry method and 50 to 70 Ag of protein were then subjected to immunoblot analysis as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Accumulating evidence indicates that silibinin has anticancer activity in various tumor cells, including cancers of prostate (5)(6)(7)(8)(9), breast (10,11), skin (12), colon (13), lung (14), kidney (15,16), and bladder (17)(18)(19)(20). There is increasing interest in elucidating the mechanisms of action for silibinin as an effective agent for chemoprevention and chemotherapy against various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Both UVA and UVB cause wavelength-dependent damage to human skin including skin cancer, whose incidence is dramatically increasing [8] . Recent studies showed that silymarin constituents could strongly protect against photocarcinogenesis and inhibit UVB and chemical tumor promoterinduced skin inflammation and edema [1,[9][10][11] . Silymarin also attenuates UVA-induced damage to human keratinocytes [12] .…”
Section: Introductionmentioning
confidence: 99%